Mini thermal cracking plant of vegetable oils for isolated communities of small farmers: operational evaluation of a prototype - Felici, Paulo Henrique Nardon; Borges, José Luiz Bernardo; Ralisch, Ricardo; Gazzoni, Décio Luiz; Ávila, Márcio Turra de (Semina: Ciências Agrárias, 2009)
A mini plant for transforming vegetable oils into biofuel, on a small scale, was developed by the Universidade de Brasília (UnB), associated to the Empresa Brasileira de Pesquisa Agropecuária (Embrapa). The technological route used was pyrolysis, that compared to the transesterification process, presented advantages of not required alcohol as reagent or sodium or potassium hydroxide as catalyst. The feedstock used for all tests was refined soybean oil. The main objective was to describe and to evaluate the mini plant instalation and operation, as well as the precautions and safety steps for its operation and maintenance. The mini plant underwent several physical changes and some aspects were optimized. The source for the heat system was changed, a new sealing system was developed to control the leakage on the distillation tower, a vegetable oil pre-heater was added to the process and solutions to minimize the volatile emissions in the environment were incorporated. For the mini plant safe operation and maintenance, individual protection equipments (IPEs) were listed and required. The mini plant is still being improved and after each new modification, the biofuel samples collected are getting closer to the technical specification, as well as the mini plant whole operation has been optimized. The biofuel viscosity is still out of specification of the Agência Nacional de Petróleo (ANP) for diesel fuel and new changes are being incorporated to the process to overcome this non-conformity.